2014
DOI: 10.1007/s00247-014-3197-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of PET/CT instead of CT-only when planning for radiation therapy does not notably increase life years lost in children being treated for cancer

Abstract: Using FDG-PET/CT instead of CT only when defining the target volumes for radiation therapy of children with cancer does not notably increase the number of life years lost attributable to diagnostic examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…64 For the 11 patients in the study at hand, effective PET/CT doses were on average 30 mSv and the 18 F-FDG PET contributed with approximately 25-30% of that. Regardless, unnecessary radiation dose should always be avoided, and it is therefore important to thoroughly assess the value as well as the risks of including 18 F-FDG PET in radiotherapy planning.…”
Section: Plan Quality and Risk Estimationsmentioning
confidence: 93%
“…64 For the 11 patients in the study at hand, effective PET/CT doses were on average 30 mSv and the 18 F-FDG PET contributed with approximately 25-30% of that. Regardless, unnecessary radiation dose should always be avoided, and it is therefore important to thoroughly assess the value as well as the risks of including 18 F-FDG PET in radiotherapy planning.…”
Section: Plan Quality and Risk Estimationsmentioning
confidence: 93%
“…A study on oncology patients conducted by Khamwan et al (2010) reported an average PET dose of 4.4 mSv and a CT dose of 14.5 mSv (contributing 77% of the total effective dose) [11]. A recent study on pediatric patients by Kornerup et al (2015) found that an average of CT effective dose of 35.0 mSv, accounting for 75% of the total effective dose from PET/CT scans that have high-resolution diagnostic quality [2].…”
Section: Dosimetry Of Pet/ctmentioning
confidence: 99%
“…The relationship between ionizing radiation exposure and radiation-induced disease is becoming increasingly noteworthy. The health risks of ionizing radiation exposure from medical imaging studies have become an important issue, drawing attention from both medical professionals and the public during the past 30 years [2] [12] [13].…”
Section: Radiation-induced Health Riskmentioning
confidence: 99%
See 2 more Smart Citations